IDENTIFIKASI PERSEBARAN LITOLOGI DAN FLUIDA RESERVOAR BATUPASIR MENGGUNAKAN ANALISIS SEISMIK INVERSI IMPEDANSI ELASTIK DAN LAMBDA-RHO DI LAPANGAN NAJLAA FORMASI CIBULAKAN CEKUNGAN JAWA BARAT UTARA - , HARSANO JAYADI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An inversion has been carried out againts the seismic data of PSTM 3D at Najlaa field in the Northern West Java basin. The method used is elastic impedance and lambda-rho inversion to identify lithology and hidrocarbon distribution of sandstones reservoir in the layer of Cibulakan Formation, Z.2210. AVO inversion has been carried out to get intercept, gradient, elastic impedance reflectivity, lambda-rho reflectivity, near angle stack, and angle stack. The AVO graph analyzing and angle stack attribute are used to determine amplitude response of the offset used to determine AVO anomaly class. From the result of sensitivity analysis showed that elastic impedance has the most sensitivity in the separation of sandstones lithology and mudstones in the angle of 30 degree. It is approved in the mapping of lithology and fluid distribution. Further crossplot analysis has been carried out between elastic impedance log angle in 30 degree againts gamma ray log to distinguish sandstones lithology and crossplot between lambda-rho log to gamma ray log to determine the indication of hidrocarbon fluids. The result of AVO analysis showed the response in the layer Z.2210 included in IIp AVO anomaly located at twt 1794 ms to 1799 ms in UI-10 well logging. Elastic Impedance mapping 30 degree inline 1141 showed that target zone of sandstones lithology has a value of 1410 (m/s)2*gr/cc to 1570 (m/s)2*gr/cc with region spread of the sandstones distribution in reservoir layers Z.2210 which has an orientation toward Northeast-Southwest. The mapping of lambda-rho inversion inline 1141 showed the indication of hidrocarbon fluids in the target zone having value about 40 MPa*gr/cc to 65 MPa*gr/cc with sandstones lithology region at reservoir layer Z.2210 which has an orientation toward North- Southeast. Hence it is proposed new drilling well at point A (inline 1230, crossline 4225), at point B (inline 1255 crossline 4310), at point C (inline 1180 crossline 4340), and at point D (inline 1155 crossline 4335) having the depth between 2316 meter to 2320 meter from surface.